Impact of varying the length of acoustic resonator on standing waves in acoustic energy harvesting / Muhammad Hatifi Mansor ... [et al.] - Mansor, Muhammad Hatifi; Mohd Sani, Mohd Shahrir; Hassan, Mohd Firdaus; Yunus, Mohd Azmi; Mutra, Rajasekhara Reddy (UiTM Press, 2025)
The study takes a unique approach by investigating how the generation and amplitude of standing waves within an acoustic resonator are affected by length changes. Using a finite element model, this study simulated standing waves inside resonators of varying lengths. The standing waves inside acoustic resonators that could be lowered from 100 cm to 20 cm with a 10 cm decrease were assessed. The results indicate that the generation and amplitudes of the low-frequency standing wave mode are directly influenced by the length of an acoustic resonator. The standing waves decreased, and the frequency shifted proportionally with changes in length. Although the total acoustic pressure amplitude decreased with changes in length, at a length of 40 cm, slightly broader results were obtained based on the voltage output circuit. Variations in the length of the acoustic resonator tube led to modifications in standing waves and natural frequency. The findings demonstrate the significant influence that acoustic factors can have on the dynamic response of acoustic energy harvesting with components made of resonator tubes.